1983
DOI: 10.1159/000153374
|View full text |Cite
|
Sign up to set email alerts
|

Group-Specific Component and Haptoglobin Phenotypes in Multiple Myeloma

Abstract: The distribution of phenotypes and gene frequencies of the group-specific component (Gc) and haptoglobin (Hp) were studied in 169 and 177 patients with multiple myeloma, respectively. The statistical analysis of our findings in comparison to the frequency of these genes in the general population does not support any correlation between the distribution of these phenotypes and the multiple myeloma or its immunological classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The lack of association between HP and myeloma reported by Germenis et al [1983], based upon a much larger sample of patients, has been confirmed by the present investigation. Clearly, the HP po lymorphism, at least that which was re vealed through starch gel electrophoresis, plays no role in the aetiology of the dis ease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The lack of association between HP and myeloma reported by Germenis et al [1983], based upon a much larger sample of patients, has been confirmed by the present investigation. Clearly, the HP po lymorphism, at least that which was re vealed through starch gel electrophoresis, plays no role in the aetiology of the dis ease.…”
Section: Discussionsupporting
confidence: 87%
“…No asso ciations have been found with antigens of the ABO system [Festen et al, 1976;Lud wig and Mayr, 1982], haptoglobin (HP) and GC (group specific component) types [Germenis et al, 1983] and Km allotypes [Ludwig and Mayr, 1982], Ludwig and Mayr [1982] reviewed the data on associa tion studies with the HLA system and con cluded that a significant association, al though weak, exists with HLA-B5 but none of the other suggested associations could be confirmed. The present study in vestigates the distribution of HP and transferrin (TF), both of which are acutephase reactant serum proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Fröhlander (1984) found no association between Hp phenotypes and leukemia but observed a significantly higher frequency of ahaptoglobinemia in these patients. A low Hp2-2 frequency has been observed in patients with IgA myeloma (Germenis et al, 1983).…”
Section: Cancermentioning
confidence: 97%
“…Associations between Hp type and dis eases such as phenylketonuria [Hsia et al, 1969], chronic leukemia [Latner and Zaki, 1969], Alzheimer's disease and senile de mentia [Op de Velde and Stam, 1973], de pression spectrum disease [Tanna et al, 1979] , retinal detachment [Padma et al, 1980] and schizophrenia [Rudduck et al, 1985] have been reported. No correlation between Hp type and disease was reported in other studies of anomalies such as schi zophrenia [Lovegrove and Nicholls, 1965], cardiac infarction, psoriasis, colon cancer, cholelithiasis, gastric ulcers and neurodermitis [Ihm and Wendt, 1966], diabetes mellitus, acute and chronic hepatitis, liver cirrhosis, psoriasis vulgaris [Jorgensen and Hopper, 1967], pulmonary tuberculo sis [Jorgensen and Rubberdt, 1968], Down's syndrome [Ball et al, 1972], can cer [Baksi et al, 1976], manic depressive disorder [Johnson et al, 1981], multiple myeloma [Germenis et al, 1983] and de mentia of Alzheimer type and multi-in farct dementia [Frohlander and Adolfson, 1985], This report presents the results of an investigation of Hp types in 320 Black individuals screened for hemoglobino pathies. …”
Section: Introductionmentioning
confidence: 98%